An Analysis of Figurative Language Popular Song Lyrics By Taylor Swift’s - Della Maharani Shalsabila; Dewi Ismu Purwaningsih; Muhammad Yassin (Nusantara Journal of Multidisciplinary Science, 2025)
This research presents an analysis of figurative language on six popular song lyrics which are “Anti-Hero”, “Lover”, “Cruel Summer”, “Shake It Off”, “Blank Space” and “Love Story” from Taylor Swift's songs. In this study, the analysis focuses in two types between comparative (including personification and metaphor) and contradictive (including hyperbole and paradox). The objective of this study is to analyse the types and meanings of figurative language. The aim is to identify the types and meanings of figurative language in six popular song lyrics. This research is descriptive qualitative research which is aimed to make the description of the analyses systematically describe the data to obtain accurate and actual results. The research data used were 6 Taylor Swift’s popular song lyrics. By using figurative language used by Taylor Swift’s that can reveal the layers of meaning hidden in the song lyrics. The data analysis is reading and identifying data, classifying data, analysing data, and making conclusion. The findings of this research show that the analysis of figurative language popular song lyrics in 6 songs used found 28 song lyrics there are personification with 2 lyrics, metaphor with 19 lyrics, hyperbole with 2 lyrics, and paradox with 5 lyrics. The dominant figurative language in this research is metaphor because metaphor helps to describe or express something in more interesting and imaginative way. And the researcher also found some emotional expression, such as love, resilience, introspection, and storytelling in Taylor Swift’s music. This research is expected to make a significant contribution to the field. The research is expected to provide readers and future researchers with a better understanding of the different types of figurative language